Regional Industrial Effects in Germany from a Potential Gas Deficit - Robert Lehmann; Christoph Schult (Center for Economic Studies and ifo Institute (CESifo), 2023)
We estimate potential regional industrial effects in case of a threatening gas deficit. For Germany, the reduction leads to a potential decrease in industrial value added by 1.6%. The heterogeneity across German states is remarkable, ranging from 2.2% for Rhineland-Palatinate to 0.7% for Hamburg. We emphasize the need for regional input-output tables to conduct economic analysis on a sub-national level, particularly when regional industrial structures are heterogeneous. The approximation with national figures can lead to results that differ both in magnitude and relative regional exposure. Our findings highlight that more accurate policy guidance can be achieved by improving the regional database.
Keywords: R11; R15; R19; 330; gas shortage; input-output analysis; regional economic impacts; Germany